2020
DOI: 10.1177/1535370220978899
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and ultrasensitive detection of circulating human papillomavirus E7 cell-free DNA as a cervical cancer biomarker

Abstract: Circulating cell-free DNA (cfDNA) has attracted attention as a non-invasive biomarker for diagnosing and monitoring various cancers. Given that human papillomavirus (HPV) DNA integration and overexpression of E6/E7 oncogenes are pivotal events for carcinogenesis, we sought to determine if HPV E7 cfDNA could serve as a specific biomarker for cervical cancer detection. We applied droplet digital PCR (ddPCR) to quantify HPV16/18 E7 cfDNA from the serum of patients with cervical cancer, cervical intraepithelial ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 78 publications
(98 reference statements)
6
20
1
Order By: Relevance
“…Several issues may explain these variable fin-dings. Firstly, there is a great variation in the methods used to detect ccfHPV DNA [ 15 , 31 , 32 , 34 , 35 , 36 , 37 , 39 , 40 , 41 , 42 , 43 , 53 ]. Since ddPCR offers a very high sensitivity and enables an absolute target quantification of the molecular target [ 52 ], this method is the obvious choice to determine the diagnostic performance of ccfHPV DNA for early detection of cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several issues may explain these variable fin-dings. Firstly, there is a great variation in the methods used to detect ccfHPV DNA [ 15 , 31 , 32 , 34 , 35 , 36 , 37 , 39 , 40 , 41 , 42 , 43 , 53 ]. Since ddPCR offers a very high sensitivity and enables an absolute target quantification of the molecular target [ 52 ], this method is the obvious choice to determine the diagnostic performance of ccfHPV DNA for early detection of cervical cancer.…”
Section: Discussionmentioning
confidence: 99%
“…So far, there has been limited success in detecting ccfHPV DNA in plasma or serum, which has mainly been suggested to be caused by a lack of sensitivity of the me-thods used [ 32 , 33 , 34 ]. Recent studies have examined the use of digital droplet PCR (ddPCR) to measure ccfHPV DNA [ 31 , 35 , 36 , 37 ]. This method is based on partitioning of the sample in many reaction chambers or droplets [ 38 ], and it offers better sensitivity and quantification of poorly abundant nucleic acids, including ccfHPV DNA [ 17 , 31 , 32 , 39 , 40 , 41 , 42 , 43 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that our methods can detect pork DNA down to 2–5 copies µL –1 with 100% detection rate (data not shown). This result was in agreement with other publications for the LOD of ddPCR (Hindson et al ., 2011; Carolina et al ., 2020; Rungkamoltip et al ., 2021; Vishnuraj et al ., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…It can also be detected either by assaying for circulating viral antigens or antibodies directed against the virus [ 102 ] or the presence of the viral genome in the bloodstream [ 103 ]. Studies have mainly focused on detecting specific viral oncogenes in the plasma using PCR-derived methods, for example, quantitative PCR (qPCR) [ 103 ], digital PCR (dPCR) [ 104 , 105 ], and droplet digital PCR (ddPCR) [ 106 , 107 ]. Detection of the viral genome to assess MRD has shown interesting results, especially in Human Papilloma Virus (HPV)-derived and Epstein–Barr (EBV)-derived cancers.…”
Section: Methodology To Detect Minimal Residual Disease With Ctdnamentioning
confidence: 99%